2001
DOI: 10.5034/inquiryjrnl_38.4.381
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Managed Care on the Use of Outpatient Mental Health and Substance Abuse Services in Puerto Rico

Abstract: This paper estimates the impact of managed care on use of mental health services by residents of low-income areas in Puerto Rico. A quasi-experimental design evaluates the impact of a low capitation rate on a minority population using three waves of data from a random community sample. Results indicate that two years after introducing managed care, privatization of mental health services had minimal impact on use. Advocates had hoped health care reform would increase access in comparison to access seen within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Lay interviewers collected the data through face to face interviews. In-depth details of the study design and subject selection criteria have been published previously [29, 30]. …”
Section: Methodsmentioning
confidence: 99%
“…Lay interviewers collected the data through face to face interviews. In-depth details of the study design and subject selection criteria have been published previously [29, 30]. …”
Section: Methodsmentioning
confidence: 99%
“…In practice, hospital services sometimes change little, and care providers such as doctors and nurses continue to work in much the same way as before. For example, McGuire et al [2] studied the effects of privatization of outpatient mental health and substance abuse services in Puerto Rico, finding that privatization had minimal impact on use. Clark et al [6] reviewed evidence on differences in the performance of care provider agencies that ranged from fully government-owned to fully private, and noted no obvious differences in performance in terms of ownership.…”
Section: Advantages and Disadvantages Of Corporatizationmentioning
confidence: 98%
“…Medicaid managed care programs in 47 states have mental health components (McFarland, 2000;Rothbard et al, 2002). Studies in Arizona (Leff, Mulkern, Lieberman, & Raab, 1994), Colorado (Bloom et al, 2002;Warner & Huxley, 1998), Massachusetts (Dickey et al, 2003), Nebraska (Bouchery & Harwood, 2003), Pennsylvania (Rothbard, Kuno, Hadley, & Dogin 2004), and Puerto Rico (Alegrie, McGuire, & Vera, 2001a;Alegrie et al 2001b) suggested there was little impact from converting fee for service Medicaid mental health to managed care. However, work in Florida (Boothroyd, Shern, & Bell, 2002), Minnesota (Lurie, Moscovice, Finch, Christianson, & Popkin, 1992), Tennessee (Chang et al, 1998;Ray, Daugherty, & Meador, 2003), Utah (Manning, Liu, & Stoner, 1999), and Virginia (Morrissey, Stroup, Ellis, & Merwin, 2002) raised concerns about the impact of Medicaid managed care on clients with serious mental disorders such as schizophrenia.…”
Section: Introductionmentioning
confidence: 95%